Preparation and Characterization of Aluminum Composite Closed-Cell Foams - Elbir, Semih; Güden, Mustafa (Izmir Institute of Technology, 2001)
An experimental study has been conducted to investigate the feasibility of the production of SiC-particulate (SiCp) reinforced Al (Aluminum) closed-cell foams using the foaming from powder compacts process and to determine the effect of SiCp addition on the foaming behavior of Al compacts and the mechanical properties of Al foams.The foaming behavior of SiCp/Al composite powder compacts and the compression mechanical behavior of SiCp/Al composite foams were determined and compared with those of pure Al compacts and Al foams prepared by the same processing parameters.Composite and Al powder compacts were prepared by hot uniaxial compaction inside a steel die at 425 oC for 1/2 hour under a constant die pressure of 220 MPa.Compacts of 99 % dense with a small amount of blowing agent of TiH2 (0.5 wt%) were heated above the melting temperature of Al inside a pre-heated furnace. During heating, as the TiH2 decomposed and released hydrogen, the compact expanded uniaxially. Foamed/partially foamed samples were taken from the furnace at the specified furnace holding times and their heights were measured in order to calculate linear expansion.Initial foaming experiments with Al compacts at 750 and 850 oC have shown that foaming at the former temperature was slower and more controllable, although linear expansion was similar at both temperatures. From these experiments, it was also found that rapid cooling of the liquid metal was necessary in order to maintain the liquid foam structure in the solid state.Foaming experiments of SiCp/Al and Al compacts at 750 oC have shown that SiCp addition a) increased linear expansion of the powder compacts and b) reduced the extent of liquid metal drainage. SiCp addition also increased the plateau stress and energy absorption capability of the Al foams. These results have shown the potential of composite foams for tailoring energy absorption of Al foams for varying levels of impact stresses.Foaming experiments have also been conducted on aluminum oxideparticulate/Al and SiC-whisker/Al composites compacts prepared using the same compaction parameters and foamed at the same temperature, 750 oC.
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 2001
Includes bibliographical references (leaves: 43-47)
Text in English; Abstract: Turkish and English
ix, 47 leaves
Keywords: TA418.9.F6 E43 2001; Foamed materials; Metal foams; Aluminum foam